Interfaz de adquisición de datos de una red de sensores por medio de un sistema embebido basado en microcontrolador PIC32 con comunicación USB - Vernavá-Amador, José Pablo; García-Ramírez, Carlos (Instituto Tecnológico de Costa Rica. Escuela de Electrónica, 2010)
The acquisition of data from a network of sensors to measure weather variables for agriculture can become an important and useful tool to develop efficient cropping plans. By having a database of weather patterns in a specific area, called microclimate, it is possible to increase the productivity of that area and obtain a better use of available resources both human and natural. This document presents an analytic description of the development of an embedded system based on PIC32 microcontroller to acquire data from a sensor network composed mainly of weather type sensors. The embedded system is capable of collecting and transmitting data through a USB port to a computer, in which the user can create their own database and may be able to view the data. Among the features of this system is its low cost, making it a viable solution for small and medium producers who do not have a tool to help them improve production, quality and resistance of a crop.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2010.
Keywords: Conversión analógico-digital; Microclima; Microcontrolador PIC32; Puerto USB; Sistema embebido; Analog-digital conversion; Red de sensores; Climatic variables; Embedded system; SB port; Microclimate; Sensor network; PIC32 microcontroller; Variables climatológicas